Controlled alternate quantum walks based privacy preserving healthcare images in Internet of Things. (April 2020) - Abd EL-Latif, Ahmed A.; Abd-El-Atty, Bassem; Abou-Nassar, Eman M.; Venegas-Andraca, Salvador E.
Highlights: Novel image encryption based on quantum walks is proposed. It designed for privacy preserving healthcare images in IoT. It has high efficiency, higher key space as well as high security. Several tests proved that the proposed approach is robust and efficient. Abstract: The development of quantum computers and quantum algorithms conveys a challenging scenario for several cryptographic protocols due to the mathematical scaffolding upon which those protocols have been built. Quantum walks constitute a universal quantum computational model which is widely used in various fields, including quantum algorithms and cryptography. Quantum walks can be utilized as a powerful tool for the development of modern chaos-based cryptographic applications due to their nonlinear dynamical behavior and high sensitivity to initial conditions. In this paper, we propose new encryption mechanism for privacy preserving Internet of Things-based healthcare systems in order to protect the patients' privacy. The encryption/decryption processes are based on controlled alternate quantum walks. The proposed cryptosystem approach is composed of two phases: substitution and permutation, both based on independently computed quantum walks. Simulation results and numerical analysis of our data provide enough evidence to reasonably conjecture that our image encryption protocol is robust and efficient for protecting patients' privacy protection.